Pengembangan LKPD Berbasis Problem Based Learning Pada Materi Gelombang Elektromagnetik Untuk Peserta Didik Kelas X SMA/MA - warti, yuli; hurriyah, hurriyah (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2019)
The purpose of this development is to produce teaching material products in the form of LKPD based on Problem Based Learning on Electromagnetic Wave material for high school class X students who are valid, practical, and effective. The development model of this study is the 4-D development model, define, design, develop, and disseminate. Research is limited to reaching the development stage due to time constraints.From the results of the assessment obtained the value of validity for the eligibility of the content is 87.33. Judging from the suitability of the learning method, the results of validity were obtained 82.28. Viewed in terms of conformity with didactic conditions, the results of 72 validity are obtained with valid categories. Viewed in terms of conformity with the terms of construction (language) obtained the results of validity 88.8 with a very valid category. While in terms of conformity with technical requirements (graphics) the value is 82.66 with a very valid category. From the results of the practicality test results obtained with the practical value of 86.37 by students in a very practical category and by the teacher obtained the results of 88.23 with a very practical category.